In this HackerEarth Smallest subarrays problem solution, You are given two arrays A and B of length N.

For every index i in array A, find the length of the smallest subarray starting from index i such that there exist at least B[i] elements with a value greater than or equal to A[i] in the subarray. If no such subarray exists, then print -1.

## HackerEarth Smallest subarrays problem solution.

```#include<bits/stdc++.h>
#define ll long long int
using namespace std;

vector<int> merge(vector<int>& v1, vector<int>& v2)
{
int i = 0, j = 0;

vector<int> v;

while (i < v1.size() && j < v2.size()) {
if (v1[i] <= v2[j]) {
v.push_back(v1[i]);
i++;
}
else {
v.push_back(v2[j]);
j++;
}
}

for (int k = i; k < v1.size(); k++)
v.push_back(v1[k]);
for (int k = j; k < v2.size(); k++)
v.push_back(v2[k]);
return v;
}

void buildTree(vector<int>* tree, int* arr,
int index, int s, int e)
{

if (s == e) {
tree[index].push_back(arr[s]);
return;
}

int mid = (s + e) / 2;
buildTree(tree, arr, 2 * index, s, mid);
buildTree(tree, arr, 2 * index + 1, mid + 1, e);

tree[index] = merge(tree[2 * index], tree[2 * index + 1]);
}

int query(vector<int>* tree, int index, int s,
int e, int l, int r, int k)
{

if (r < s || l > e)
return 0;

if (s >= l && e <= r) {
return (tree[index].size()
- (lower_bound(tree[index].begin(),
tree[index].end(), k)
- tree[index].begin()));
}

int mid = (s + e) / 2;
return (query(tree, 2 * index, s,
mid, l, r, k)
+ query(tree, 2 * index + 1, mid + 1,
e, l, r, k));
}

void solve()
{
int n;
cin >> n;
assert(1 <= n and n <= 300000);

int a[n];
for(int i = 0 ; i < n ; i++)
{
cin >> a[i];
assert(1 <= a[i] and a[i] <= 1000000000);
}

int b[n];
for(int i = 0 ; i < n ; i++)
{
cin >> b[i];
assert(1 <= b[i] and b[i] <= n);
}

vector<int> tree[4*n+1];
buildTree(tree, a, 1 , 0 , n - 1);

for(int i = 0 ; i < n ; i++)
{
int value = a[i];
int s = i;
int e = n - 1;
int ans = -1;

while(s <= e){
int m = (s+e) >> 1;
int cnt = query(tree, 1, 0, n - 1, i, m, value);

if(cnt >= b[i])
{
ans = m;
e = m - 1;
}
else{
s = m + 1;
}
}

if(ans == -1) cout << ans << " ";
else cout << (ans - i + 1 ) << " ";
}
cout << endl;
}

int main(){
ios_base::sync_with_stdio(false);
cin.tie(NULL);
int t;
t = 1;
while(t--)
{
solve();
}
}```